Habit, Story, Delight: Essential Tools for the Public Service Advocate - Jean Koh Peters (Washington University Journal of Law & Policy, 2001)
This Essay is a compilation of stories and reflections about the life of a public service lawyer.
Keywords: Legal assistance to the poor; Advice; Public interest